Does Religiosity influence Takaful Participation? - Hartini, Ab Ghani; Salman, Lambak (2016)
Malaysia is a multicultural and multiconfessional country. As of the 2010 Population and Housing Census, 61.3 percent of the population practices Islam; 19.8 percent Buddhism; 9.2 percent Christianity; 6.3 percent Hinduism; and 1.3 percent traditional Chinese religions. The religion with element of haram prohibition is Islam. It is a religion governed by rules and customs built on the five pillars; the five basic acts in Islam which is mandatory by believers and are the foundation of Muslim life: shahadah (witnessing); salat (prayer); zakah or charity; sawn or fasting, and hajj or pilgrimage. Malaysia’s Takaful (Islamic insurance) has significant opportunities for growth as its penetration rate is still low at 5.2% of gross domestic product (GDP). The low penetration rate of takaful in the country is due to the lack of awareness on takaful-related products as well as the issue of affordability, especially among the lower group segments of the society. The objective of this paper is to examine the relationship between religious commitment and Takaful participation. The samples were selected consisting of conventional life insurance policyholders residing in East Coast region Malaysia. The findings indicate that although religious commitment influence Takaful participation, there are other factors restrict the participation.